The sulfoxidation reaction catalyzed by CoBr2 complexes, under the magnifying glass of green parameters - Pinilla Peña, Diana Carolina (2018)
Different cobalt (II) and nickel (II) species were used as catalysts in sulfoxidation reactions giving excellent yields and high chemoselectivity. Among the cobalt (II) species, both γ-cyclodextrin complexes synthesized in ethyl acetate or dichloromethane solvents were very good catalysts, while γCDNiBr2 synthesized in ethyl acetate was the best of Ni (II) species. Sulfoxidation takes place with high chemoselectivity in the presence of other groups such as aldehyde. Good results were obtained when these reactions were analyzed using green chemistry metrics. Techniques as FT-IR, UV?vis Diffuse Reflectance, colorimetry, TGA, flame atomic absorption, potentiometric halide titration, and elemental analysis were used to characterize novel complexes. The change of solvent in the synthesis of complexes produces positive effects in holistic green metrics.